Effect of intermittent fasting on behavioral, biochemical and histopathological parameters in rats under Acrylamide exposure - Arihan, Okan; Dagli Gul, Asli San; Akkoyun, Hurrem Turan; Akkoyun, Mahire; Uyar, Ahmet; Kutlu, Tuncer; Dastan, Ahmet Onur; Erdem, Aysen; Ozgur, Sezgi Firat (Revista Científica de la Facultad de Ciencias Veterinarias, 2026)
Acrylamide is a known neurotoxic and potentially carcinogenic compound. It remains as a major public health concern due to its widespread presence in heat-processed foods. Despite extensive research on acrylamide-induced toxicity, effective dietary strategies to mitigate its harmful impact remain limited. Intermittent fasting has recently emerged as a promising metabolic intervention shown to enhance cellular stress resistance and improve antioxidant capacity. This study was designed to investigate the effects of intermittent fasting on acrylamide-induced toxicity in rats. Wistar rats were randomly divided into four groups: control, acrylamide, intermittent fasting, and acrylamide + intermittent fasting. Intermittent fasting was applied every other day, while acrylamide was administered intraperitoneally at a dose of 30 mg/kg/day, three times per week. On day 28, behavioral assessments were performed using the Elevated Plus Maze, Open Field Test, hotplate, and rotarod tests. Biochemical analyses were conducted on blood samples, and oxidative stress parameters Catalase, Glutathione peroxidase, Superoxide dismutase were measured in liver, kidney, and brain tissues. Histopathological evaluations were also carried out. Histopathological findings indicated tissue damage in the acrylamide group and partial improvement in the acrylamide + intermittent fasting group. In the rotarod test, performance of the acrylamide + intermittent fasting group was similar to the control group, suggesting a protective effect. Catalase, Glutathione peroxidase, and Superoxide dismutase levels showed partial amelioration in kidney and brain tissues due to intermittent fasting. The results suggest that intermittent fasting may exert a protective effect against acrylamide-induced oxidative stress and behavioral impairments in rats. These findings highlight the potential of intermittent fasting as a non-pharmacological strategy to mitigate acrylamide toxicity.